2022
DOI: 10.1021/acs.est.2c03584
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Source Apportionment of Atmospheric Alkaline Gases in Urban Beijing

Abstract: Alkaline gases, including NH3, C1–3-amines, C1–3-amides, and C1–3-imines, were measured in situ using a water cluster-CIMS in urban Beijing during the wintertime of 2018, with a campaign average of 2.8 ± 2.0 ppbv, 5.2 ± 4.3, 101.1 ± 94.5, and 5.2 ± 5.4 pptv, respectively. Source apportionment analysis constrained by emission profiles of in-use motor vehicles was performed using a SoFi-PMF software package, and five emission sources were identified as gasoline-powered vehicles (GV), diesel-powered vehicles (DV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Dimethylamine (DMA) was presumed to be the base solely responsible for particle formation, and the emissions of DMA are presumed to scale with those of NH 3 . Particle formation in Beijing and similar cities has indeed been shown to be driven by DMA; , however, should DMA concentrations decrease, other amines may drive NPF (such as monoethanolamine, an important amine during carbon capture for which we provide estimates of J A4B4 in Figure S2), or trimethylamine, which has recently been shown by source apportionment to have distinct sources from DMA . All VOCs are presumed to scale equally, both those capable and incapable of forming and growing new particles.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Dimethylamine (DMA) was presumed to be the base solely responsible for particle formation, and the emissions of DMA are presumed to scale with those of NH 3 . Particle formation in Beijing and similar cities has indeed been shown to be driven by DMA; , however, should DMA concentrations decrease, other amines may drive NPF (such as monoethanolamine, an important amine during carbon capture for which we provide estimates of J A4B4 in Figure S2), or trimethylamine, which has recently been shown by source apportionment to have distinct sources from DMA . All VOCs are presumed to scale equally, both those capable and incapable of forming and growing new particles.…”
Section: Resultsmentioning
confidence: 84%
“…Particle formation in Beijing and similar cities has indeed been shown to be driven by DMA; 20 , 23 however, should DMA concentrations decrease, other amines may drive NPF (such as monoethanolamine, an important amine during carbon capture 50 for which we provide estimates of J A4B4 in Figure S2 ), or trimethylamine, which has recently been shown by source apportionment to have distinct sources from DMA. 51 All VOCs are presumed to scale equally, both those capable and incapable of forming and growing new particles. No other compounds (such as HNO 3 ) are considered to contribute to the particle growth.…”
Section: Resultsmentioning
confidence: 99%
“…Motor vehicle emission is one of the important mobile sources. 63,73,98 Feng et al observed that the widely used ethanol gasoline vehicles in Hebei Province, China can primarily emit EAs. 63 Yang et al further compared the amine emission strengths of different power sources, and found that the total emission strength of diesel trucks was the greatest followed by those of gasoline cars and natural gas cars.…”
Section: Source Apportionment Of Atmospheric Aminesmentioning
confidence: 99%
“…A regional or global bottom-up emission inventory of DMA is currently lacking, mostly due to scarce direct measurements (Yang et al, 2022;Zhu et al, 2022). In previous 3D model studies, amine/NH3 emission ratios have often been used to estimate amine emissions due to the close correlation between NH3 and DMA emissions.…”
Section: Sources and Sinks Of Dimethylamine In The Updated Wrf-chem/r...mentioning
confidence: 99%